2016
DOI: 10.1016/j.jsxm.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Non-Suicidal Self-Injury Among Trans Youth

Abstract: Risk Factors for Non Suicidal Self Injury among Trans Youth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 46 publications
(65 reference statements)
9
104
1
4
Order By: Relevance
“…These high rates are consistent with recent studies on individuals who identify as transgender (Arcelus, Claes, Witcomb, Marshall, & Bouman, 2016; Bockting, Miner, Swinburne Romine, Hamilton, & Coleman, 2013; Dawson, Wymbs, Gidycz, Pride, & Figueroa, 2017), with our large and diverse data set underscoring the major needs of transgender individuals during college. Psychological factors like the expectation of rejection may lead students to feel unworthy and unsafe, leaving them more susceptible to MH challenges compared to their counterparts who classify as cisgender (Bouman et al, 2017; Denton, Rostosky, & Danner, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…These high rates are consistent with recent studies on individuals who identify as transgender (Arcelus, Claes, Witcomb, Marshall, & Bouman, 2016; Bockting, Miner, Swinburne Romine, Hamilton, & Coleman, 2013; Dawson, Wymbs, Gidycz, Pride, & Figueroa, 2017), with our large and diverse data set underscoring the major needs of transgender individuals during college. Psychological factors like the expectation of rejection may lead students to feel unworthy and unsafe, leaving them more susceptible to MH challenges compared to their counterparts who classify as cisgender (Bouman et al, 2017; Denton, Rostosky, & Danner, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…This corresponds with higher rates of reported self-harm in females than males in general population studies (8.9% vs 5.7%; McManus et al, 2016) and supporting research suggesting male transgender individuals have a higher rate of self-harm than female transgender individuals (Veale, Watson, Peter and Saewcy, 2017;Arcelus et al, 2016). There was no evidence to support the prediction that nonbinary participants would report more self-harm than binary participants, which had been based on a sample of combined male and female nonbinary participants (Veale et al, 2017).…”
Section: Self-harmsupporting
confidence: 66%
“…17, 1922, 3742 Researchers in a survey of 101 transfeminine and transmasculine patients ages 12 to 24 years in a transgender youth clinic in Los Angeles found that 35% had symptoms of depression and >50% had suicidal thoughts. 19 In comparison, we found that adolescents had a higher prevalence (40%–60%) of depression but a lower prevalence of suicidal ideation (5%–10%).…”
Section: Discussionmentioning
confidence: 99%